Regional Cooperation for the Sustainable Development and Management in Northeast Asia - Yongrok Choi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue consists of selected papers from the Sustainable Asia Conference 2017, annual international conference which was held in Nanjing, China, from 23-28 June, 2017. SAC is one of the leading international conferences presenting novel and fundamental advances in Asia's sustainable development issues. The purpose of the conference was for scientists, scholars, engineers, and students from universities and research institutes around the world to present ongoing research activities so as to promote global research networking in the area of sustainable development. This conference provides opportunities for the delegates to exchange new ideas and application experiences, face-to-face, to establish research or business relations, and to find global partners for future collaborations. The scope of this Special Issue encompassed topics related to sustainable development and management at both the macro- and micro-levels in Northeast Asian countries.